Psalms of hope : poetic exegesis of bani of Guru Tegh Bahadur - Tegh Bahadur, Guru, 1621-1675 (B.K. Tulsi, 1978)
English verse translations of the hymns (padavalis and shalokas) selected from the Adi Granth, Sikh scripture.